Winning and losing on social media: Comparing viral political posts across platforms. (June 2020) - Larsson, Anders Olof
Research on social media use during election campaigns has largely focused on Twitter. Building on recommendations from previous scholarship, the work presented here provides comparative insights into party and citizen engagement on several platforms – Facebook, Twitter, Instagram and YouTube – during the 2017 Norwegian elections. Results indicate that the themes of popular, 'viral' posts vary across platforms, suggesting the need to adapt political messages to each specific outlet. The findings are discussed in the light of the suggested 'analytics turn' – when political actors can gauge the minutiae of how their online efforts are engaged with, how do those types of insights influence the shape and content of political campaigns?